The active aging level of the rural older adults with disability in China: a cross-sectional study - Tian, Yutong; Zhang, Yan; Yan, Yuwen; Zhang, Huizhong; Li, Xizheng (Frontiers in Public Health, 2023)
Background Active aging has been listed as an important indicator to measure the quality of life of the older adults and the construction of the senior care system. There is an imbalance between the supply and demand of senior care services for the disabled older adults in rural areas, and the quality of life needs to be improved. Objectives We aimed to analyze the current situation of active aging and the influencing factors of the rural disabled older adults, in order to provide a reference basis for improving the quality of life of the rural disabled older adults. Methods We conducted a multicenter and cross-sectional study, using the Barthel Index Scale and Chinese version of the Active Aging Scale, to facilitate the selection of 304 rural older adults with disability in 26 villages under Henan Province for a questionnaire survey. Results The mean score for the level of active aging of rural older adults with disability was 1.87 (SD 0.36), with the highest score for the dimension of being self-reliant (Mean2.29, SD 0.61) and lower scores for the dimension of active contribution to society (Mean 1.37, SD 0.55) and building up financial security (Mean 1.37, SD 0.57). The results of the multiple regression analysis showed higher levels of active aging among the disabled older adults with retirement pay, mild disability, and longer time per activity/rehabilitation exercise (p < 0.05). Conclusion Active aging of the rural disabled older adults is at a low level, with insufficient economic security and social participation. The national government should help improve the quality of primary health care in rural areas, build a friendly environment for senior communities, and improve policies to protect the welfare of the older adults, so as to collaboratively empower the disabled older adults in rural areas at three levels: health, participation, and protection.